RPSR1, a major quantitative trait locus for Pythium stalk rot resistance in maize - Shengfeng He; Junbin Chen; Chuang Liu; Dandan Liu; Lei Wang; Canxing Duan; Wangsheng Zhu (Crop Journal)
Pythium stalk rot (PSR) is a destructive disease of maize, severely affecting yield and grain quality. The identification of quantitative trait loci (QTL) or genes for resistance to PSR forms the basis of disease-resistant hybrids breeding. In this study, a major QTL, Resistance to Pythium stalk rot 1 (RPSR1), was identified from a set of recombinant inbred lines derived from MS71 and POP. Using a recombinant progeny testing strategy, RPSR1 was fine-mapped in a 472 kb interval. Through candidate gene expression, gene knock-down and knock-out studies, a leucine-rich repeat receptor-like kinase gene, PEP RECEPTOR 2 (ZmPEPR2), was assigned as a PSR resistance gene. These results provide insights into the genetic architecture of resistance to PSR in maize, which should facilitate breeding maize for resistance to stalk rot.